Pengaruh Pengetahuan Kewirausahaan, Motivasi, Lingkungan Keluarga dan Media Sosial Terhadap Minat Berwirausaha Mahasiswa Muslim - Nur Ahmadi Bi Rahmani; Siti Aisyah; Salmiah Hasibuan (Journal on Education, 2023)
Efforts that can be made to reduce unemployment are by creating jobs. In creating jobs, it must be accompanied by an entrepreneurial spirit. The purpose of this study was to determine how much influence entrepreneurial knowledge, motivation, family environment and social media on entrepreneurial interest in FEBI UINSU Medan students. The method used in this research is a quantitative method with a descriptive analysis approach and a sample size of 372 people. The data obtained from distributing questionnaires will be tested with the SmartPLS 3.2 application tool. This study obtained the results of the t-value of the entrepreneurial knowledge variable of 3.873, motivation of 5.206, family environment of 5.398 and social media of 0.403 with a t-table value of 2.25. So it can be concluded that the variables of entrepreneurial knowledge, motivation and family environment have an effect while social media has no effect on the entrepreneurial interest of FEBI UINSU Medan students.